Dinotrema concinnum Haliday 1838 ... - Gadallah, Neveen S.; Ghahari, Hassan; Peris-Felipo, Francisco Javier; Fischer, Maximilian (Zenodo, 2015)
Dinotrema concinnum (Haliday, 1838) Distribution in Iran. Ilam (Ghahari et al. 2011d, Khajeh et al. 2014 as Syndalis maxima), Qazvin (Ghahari et al. 2011b as D. concinna (Haliday 1838)), Iran (no locality cited) (Yu et al. 2012; Peris-Felipo 2013; Peris-Felipo et al. 2014b). Distribution outside Iran. Afghanistan, former Czechoslovakia, Faeroe Islands, Iceland, Ireland, Mongolia, Netherlands, Poland, Russia, Sweden and Tunisia (Yu et al. 2012; Peris-Felipo 2013; Peris-Felipo et al. 2014b), Austria and Germany (Fischer 1973a; Francés and Jiménez 1989b as Synaldis maxima; Yu et al. 2012; Peris-Felipo 2013; Peris-Felipo et al. 2014b), Bulgaria and Israel (Papp 2011–2012 as S. maxima), Greece (Papp 2007a as D. concinna; Yu et al. 2012; Peris-Felipo 2013; Peris-Felipo et al. 2014b), Hungary (Fischer 1973a, Francés and Jiménez 1989b as S. maxima; Papp 2008; Yu et al. 2012; Peris-Felipo 2013; Peris-Felipo et al. 2014b), Italy (Papp 2011–2012 as S. maxima; Yu et al. 2012; Peris-Felipo 2013; Peris-Felipo et al. ... : Published as part of Gadallah, Neveen S., Ghahari, Hassan, Peris-Felipo, Francisco Javier & Fischer, Maximilian, 2015, An annotated catalogue of the Iranian Alysiinae (Hymenoptera: Braconidae), pp. 1-28 in Zootaxa 3974 (1) on page 5, DOI: 10.11646/zootaxa.3974.1.1, http://zenodo.org/record/288961 ...